THE INFLUENCE OF MACROECONOMICS ON BANKING STOCK RETURNS IN INDONESIA: A STUDY OF STATE-OWNED AND PRIVATE BANKS - Willa Fatika Sari; Ahmad Fauzi; Iis Azelya; Muhammad Hayyi Lana Alkhan; Syintia Mega Putri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the influence of macroeconomic variables on banking stock returns in Indonesia, with a comparative focus on state-owned and private banks. The macroeconomic variables analyzed include inflation, the BI Rate, and the rupiah exchange rate against the US dollar. This research applies a quantitative explanatory approach using monthly panel data from 2015 to 2025. The sample consists of six banking companies listed on the Indonesia Stock Exchange, namely three state-owned banks and three private banks, with a total of 792 observations. The data were analyzed using panel data regression through the Common Effect Model estimated by Ordinary Least Squares. The findings indicate that inflation, interest rates, exchange rates, and bank ownership simultaneously have a significant effect on banking stock returns. Partially, the BI Rate and exchange rate have a negative and significant effect on stock returns, while inflation has no significant effect. The ownership dummy shows no significant difference between the stock returns of state-owned and private banks. These results suggest that macroeconomic conditions, particularly interest rates and exchange rate movements, play a more dominant role in influencing banking stock returns than bank ownership characteristics. The study contributes to investment decision-making by highlighting the importance of monitoring monetary policy and exchange rate stability in assessing banking sector stock performance.